Implementation Of The Web-Based Maritime Security Data Integration Policy At Tanjung Uban Port - Setiawan, Adi Agus; Suharto, Didik Gunawan; Haryanti, Rina Herlina (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Indonesia, as the largest archipelagic country in the world, relies heavily on maritime transportation, which is crucial for connecting its islands and facilitating trade. With its vast maritime territory, the country faces significant challenges in ensuring the safety and security of sea transport. The implementation of effective regulations and the integration of data related to maritime safety and security are vital for minimizing risks, particularly in busy ferry ports like Tanjung Uban. This study aims to analyze the implementation of a web-based data integration policy for maritime safety and security at the Tanjung Uban Ferry Port, focusing on the integration of safety data to improve public services. Using a qualitative research approach, the study gathered data through interviews with key stakeholders such as port officials, ASDP representatives, and relevant government agencies. Data was also collected through document reviews and observations. The findings indicate that the shift from manual data management to an integrated web-based system has significantly improved communication, efficiency, and access to safety-related information across involved agencies. The integration of this data not only facilitates smoother coordination but also enhances the ability to monitor and ensure the safety of passengers and vessels. The study concludes that the successful implementation of web-based data integration has the potential to improve the quality of maritime safety and security services, providing a model for other ports in Indonesia and enhancing the overall maritime infrastructure.